Management of Searching Process in Inventory Activities - DINCA, Sorin (Journal of Advanced Research in Management, 2017)
In the last years, the library is less and less found in people’s life style. Due to the decreasing interest in the printed books as opposed to technology, which answers the people’s questions very easily, a flexible app that would not only manage the inputs and outputs from a library, but also create a bridge between the library – librarian – reader by offering the management team the possibility to deal with this bridge so that the reader crosses it as often as possible is mandatorily necessary.